Management of recurrent malignant pleural effusion in the United Kingdom: survey of clinical practice. Issue 9 (September 1990) - McAlpine, L G; Hulks, G; Thomson, N C
Abstract : Malignant pleural effusions are often symptomatic and tend to recur after simple aspiration. Pleurodesis may prevent recurrence of the effusion; many agents and techniques have been described. A questionnaire was sent to 448 clinicians in the United Kingdom to determine how pleurodesis is performed in practice. There was a 56% overall response, with replies from 101 respiratory physicians, 88 general physicians, 29 thoracic surgeons, and 35 general surgeons. General surgeons saw few cases of malignant pleural effusion and rarely performed pleurodesis. A patient with recurrent malignant pleural effusion would usually be managed with pleurodesis by 76 (76%) respiratory physicians, 26 (30%) general physicians, and 23 (81%) thoracic surgeons; a further 29 (33%) general physicians would refer such patients to another specialist. Most medical pleurodesis were performed by junior staff, whereas consultant thoracic surgeons were more likely to be concerned with the procedure. All the thoracic surgeons used an intercostal tube drain, usually with suction. An intercostal tube drain was used routinely by only 54 (54%) of the respiratory physicians and 28 (32%) general physicians. Thoracic surgeons preferred talc for pleurodesis whereas physicians most commonly used tetracycline. The variety of methods in use supports the need for randomised, controlled studies to determine the most effective technique of pleurodesis.